Role of the CD40-CD40L expression level pathway in the diagnosis of unexplained recurrent pregnancy loss - Hui Ding; Guoqian An (Taylor & Francis Group, 2023)
AbstractBackground Unexplained recurrent spontaneous pregnancy loss (URPL) lacks effective treatment and reliable early diagnosis and prediction. Immunologic dysfunction can be an underlying cause of recurrent pregnancy loss (RPL). Considering the regulatory role of CD40-CD40L in immune responses, we explored its clinical significance in URPL.Methods The 108 women with URPL who were treated in Hebei Yanda Hospital from January 2020 to December 2022 were selected as study subjects, and another 108 healthy women who were not pregnant and matched with the age and body mass index of the study group were selected as the control group. CD40 and CD4 + CD25 + Treg cells in peripheral blood mononuclear cells (PBMCs) and CD40L in peripheral blood platelets were measured by flow cytometry. The predictive value of CD40-CD40L in URPL for the risk of RPL was determined by receiver operating characteristic (ROC) curves. The correlations of CD40-CD40L with CD4 + CD25 + Treg cells and serum pro-inflammatory factors were assessed by Pearson's analysis.Results CD40 on the surface of PBMCs and CD40L on the surface of platelets were up-regulated in URPL patients. CD40 in combination with CD40L had high predictive value for the risk of RPL in URPL patients. Peripheral blood CD40-CD40L was positively linked to IL-17 and IL-23, and negatively to CD4 + CD25 + Treg cells and IL-10 in URPL patients.Conclusions The CD40-CD40L pathway expression in peripheral blood can help predict the risk of RPL in URPL patients.